Experimental research on the dynamic propagation process of mode I cracks in the rock under directional fracture blasting using the strain gauge method. (August 2020) - Li, Qing; Gao, Zheng-Hua; Xu, Wen-Long; Wang, Kai; Liu, Shuo; Ran, Guo-Feng; Hu, Yang
Highlights: The directional fracture blasting realize mode I cracks. The dynamic fracture process of rock material is studied by the strain gauge method. The strain gauge method calculate the stress intensity factor. The strain gauge method calculate crack propagation velocity. The parameters calculated by the strain gauge method are consistent with the caustics. Abstract: Based on the directional fracture blasting experiment of polymethyl methacrylate (PMMA) specimens and combined with an analysis of the strain field around the dynamic crack tip, a strain gauge method with a specific acute (obtuse) orientation is proposed to record the dynamic fracture process of mode I cracks. A time evolution of the strain of the whole test process is employed to establish a binomial expression to represent the crack tip position and surrounding strain field and calculate the crack propagation velocity (CPV) and dynamic stress intensity factor (DSIF). Compared with the dynamic caustics method, the feasibility of the strain gauge method is analyzed. The strain gauge method is employed to research the dynamic fracture process of mode I cracks in rock directional fracture blasting. The results show that when the normalized strain value is 0 in the acute orientation or the maximum in the obtuse orientation, the position of the propagating crack tip is directly below the strain gauge. The calculations of the CPV and DSIF are consistent with those of the dynamic caustics method, which verifies the feasibility of the strain gauge method. The acute orientation has a large error dispersion. Compared with the dynamic caustics method, the strain gauge method can approximately record the whole process of rock crack propagation, reveal the evolution law of the CPV and DSIF and provide an experimental basis for research on the directional fracture process of nontransparent materials. Compared with the PMMA specimens, the rock specimens have a larger oscillation of the CPV and a smaller oscillation of the DSIF.